THE URGENCE REGULATION OF BUSINESS ACTIVITIES ON ISLAMIC MICROFINANCE INSTITUTION ACCORDING LAW NO. 1 YEAR 2013 OF MICROFINANCE INSTITUTIONS - Prawitra Thalib; Sri Hajati; Faizal Kurniawan; Komari Aldiansyah (Arena Hukum, 2021)
AbstractMicrofinance Institutions (hereinafter referred to as MFIs) are financial institutions that function as intermediary institutions that aim not only to seek profit, but have another goal, namely social goals whose activities are more community development. MFIs in conducting business activities can be carried out conventionally or based on Sharia Principles. The business activities carried out by MFIs include trading activities, namely in the service sector. In carrying out Shariah MFI business activities, it must be based on Sharia Principles. The method used in writing this article is normative research with a statutory and conceptual approach. The results of the study show that the Sharia Principles in this context are guided by the basic principles of Muamalah. The important objective in this research is the regulation in the laws and regulations regarding this matter whether it is in accordance with sharia principles. Harmonization between legislation as positive law in Indonesia with sharia principles sourced from the Qur'an and Hadith as the main legal sources of Islamic law is absolutely necessary to ensure legal certainty.AbstrakLembaga Keuangan Mikro (selanjutnya disebut LKM) merupakan lembaga keuangan yang berfungsi sebagai lembaga intermediary yang bertujuan tidak hanya semata-mata mencari keuntungan (profit motive) saja, tetapi mempunyai tujuan lain yakni tujuan sosial (social motive) yang kegiatannya lebih bersifat community development.Â LKM dalam melakukan kegiatan usaha bisa dilakukan secara konvensional atau berbasis pada Prinsip Syariah. Kegiatan usaha yang dilakukan LKM termasuk dalam kegiatan perdagangan yakni dalam bidang jasa. Dalam menjalankan kegiatan usahanya LKM Syariah harus berdasarkan Prinsip Syariah. Metode yang digunakan dalam penulisan artikel ini adalah penelitian normatif dengan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan Prinsip Syariah dalam konteks ini berpedoman pada Prinsip dasar Muamalah. Tujuan dalam penelitian ini yang penting yaitu pengaturan dalam peraturan perundang-undangan terkait hal ini apakah sudah sesuai dengan prinsip syariah. Harmonisasi antara peraturan perundang-undangan sebagai hukum positif di Indonesia dengan prinsip-prinsip syariah yang bersumber pada Al-quran dan Hadist sebagai sumber hokum utama hokum islam mutlak diperlukan adanya untuk menjamin kepastian hukum.Â